Compositions, mechanical properties and microstructures of cBN-based composites sintered with Al or TiC. (4th July 2017) - Yang, Limin; Yue, Zhenming; Gong, Jianhong; Zhao, Xiaodi; Chu, Xingrong
ABSTRACT: Cubic boron nitride (cBN)-based composites were prepared from cBN–Al and cBN–TiC mixtures, respectively, under high pressure and high temperature (HPHT). During sintering, Al reacted with cBN and produced AlN and AlB2, while TiC did not react with cBN. With increasing Al from 5–20 wt-%, the strength of the cBN-based composites decreased first, then increased. AlN and AlB2 could strengthen the cBN-based composites to a certain extent. In the preparation from cBN–TiC, 10 wt-% addition of TiC was the optimal formulation to obtain the densest microstructure. Hardness of the two kinds of composites displayed different tendencies. On the other hand, cBN-based composites were treated at 1200°C for 1200 s. It was found that the isothermal oxidation process could be described by parabolic laws with slight oxidation scales formed on samples' surfaces in different morphologies.